Digital Narratives During the Pandemic: TV Series, Social Media, and Conversations on the Internet - Martínez-Borda, Rut; de-la-Fuente, Julián; Lacasa, Pilar (Frontiers in Psychology, 2021)
The pandemic has changed peoples’ lives a little. Digital communication media has not been extraneous to these changes and neither in particular have the representations people construct of its contents. This study focuses on conversations between Spanish-speakers taking place on Internet and which relate to a selection of TV series during lockdown in the pandemic provoked by COVID 19. Analysis of big data and other data was combined for the purpose of finding out how meanings were built up, from the perspective of discourse analysis. Digital texts were collected during the period between 14th March and 15th June 2020. This period coincided with the situation of strict lockdown in Spain. We examined 15,735 mentions from 7,552 users. Two hundred and sixty eight categories were defined dynamically. In this study we considered only those which were the most relevant from the research team’s viewpoint, facilitating in-depth analysis of conversations through discourse analysis. Results show that participants constructed digital, transmedia, multimodal and interactive narratives. The conversations analysed also show how the presence of contextualised factors related to the pandemic interlink with interpretations of the series.